Perovskite precursor powder, diode and preparation method thereof

The pure phase all-inorganic CsPbBr3 powder was prepared by dissolving precipitation and recrystallization, and CsBr was added to the perovskite precursor solution, and low-temperature annealing and TPBi post-treatment were solved, which solved the high defect density and low luminous efficiency of all-inorganic perovskite light-emitting diodes. , significantly improves the external quantum efficiency and brightness of the device.

CN119430271APending Publication Date: 2025-02-14TIANFU JIANGXI LAB +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411315064.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

All-inorganic perovskite light-emitting diodes have problems with low luminescence efficiency caused by high defect density and non-radiative recombination.

Method used

Pure phase all-inorganic CsPbBr3 powder is prepared by dissolving precipitation and recrystallization, and perovskite is passivated under the condition of bromine-rich, low-temperature annealing and excessive CsBr additives induce perovskite perovskite. The crystal grows along the (110) crystal plane. At the same time, the perovskite luminescent layer was post-treated using TPBi acetone solution to fill in the film defects.

Benefits of technology

It effectively improves the external quantum efficiency and brightness of perovskite light-emitting diodes, reduces film defects, and improves device performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430271A_ABST
    Figure CN119430271A_ABST
Patent Text Reader

Abstract

The invention discloses perovskite precursor powder, a diode and a preparation method of the perovskite precursor powder, and relates to the field of design and manufacturing of light-emitting diode devices. Precursor powder of the perovskite luminescent layer is prepared based on recrystallization of dissolved precipitates, cesium bromide is dissolved in deionized water, lead bromide is dissolved in hydrobromic acid with the volume fraction being 48%, solutions are prepared, the prepared cesium bromide solution is added into the lead bromide solution to form pure-phase orange precipitates, the precipitates are filtered and washed through absolute ethyl alcohol, and the perovskite luminescent layer is obtained. And drying at 60 DEG C to obtain green light perovskite luminescent layer precursor powder CsPbBr3. The perovskite light-emitting diode is prepared by pre-synthesizing the all-inorganic pure-phase CsPbBr3 powder, so that the device performance of the all-inorganic green perovskite light-emitting diode can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of light emitting diode design and manufacturing, and in particular to a perovskite precursor powder, a diode and a preparation method thereof. Background Art

[0002] Metal halide perovskite (MHP) materials are semiconductor materials with excellent optoelectronic properties that have emerged in recent years. They have the advantages of high fluorescence quantum yield (PLQY), continuously adjustable emission wavelength, narrow emission half-peak width, high color purity, adjustable band gap, solution preparation and low preparation cost. Therefore, they are widely used in the preparation of high-efficiency, flexible and green electroluminescent devices, namely perovskite light-emitting diodes (PeLEDs).

[0003] CsPbBr3 perovskite is a very promising green light-emitting material for light-emitting diodes (LEDs). However, due to the lack of suitable all-inorganic perovskite film preparation methods and interface engineering, the preparation of high-quality all-inorganic perovskite films by solution method is still very challenging, and the corresponding perovskite LED performance lags far behind that of organic-inorganic hybrid perovskite light-emitting diodes. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of high defect density and low luminous efficiency caused by serious non-radiative recombination of the current all-inorganic perovskite light-emitting diodes, and to provide a perovskite precursor powder, a diode and a preparation method thereof.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] A method for preparing an all-inorganic green light perovskite luminescent layer material, preparing a powder of a perovskite luminescent layer precursor by dissolution, precipitation and recrystallization, the method comprising the following steps:

[0007] S1. Dissolve CsBr (cesium bromide) in deionized water to prepare a CsBr solution;

[0008] S2. Dissolve PbBr2 (lead bromide) in a 48% by volume HBr solution to prepare a PbBr2-HBr solution;

[0009] S3. Add CsBr (cesium bromide) solution dropwise into PbBr2-HBr solution to form a mixed solution, wait for an orange-yellow precipitate to form in the mixed solution, continue stirring the mixed solution, and then collect the precipitate CsPbBr3 (cesium lead bromide) by suction filtration;

[0010] S4. Wash the precipitated CsPbBr3 twice with anhydrous ethanol and dry it at 60°C in a vacuum environment to obtain a dry precipitated CsPbBr3 powder as a perovskite light-emitting layer material.

[0011] Furthermore, 2.13 g of CsBr in S1 was dissolved in 5 ml of deionized water.

[0012] Furthermore, 3.65 g of PbBr2 in S2 is dissolved in 15 ml of a 48% by volume aqueous solution of hydrobromic acid.

[0013] Furthermore, the CsBr solution in S3 is added dropwise for 5 minutes.

[0014] Furthermore, the stirring time in S3 is 1 hour, and the vacuum drying time is 12 hours.

[0015] A perovskite light-emitting diode, the diode comprising an anode, a hole transport layer, a perovskite light-emitting layer, a post-processing layer, an electron transport layer, an electron injection layer and a cathode arranged in sequence from bottom to top, wherein the perovskite light-emitting layer is located between the hole transport layer and the electron transport layer;

[0016] Wherein, the structural formula of the perovskite light-emitting layer material is CsPbBr3;

[0017] Wherein, the thickness of the perovskite light-emitting layer is 60-80 nm;

[0018] Wherein, the anode comprises indium tin oxide (ITO) conductive glass;

[0019] The hole transport layer material includes one or more of poly (3,4-ethylenedioxythiophene:polystyrene sulfonate) (PEDOT:PSS), 4-butyl-N,N-diphenylaniline homopolymer (poly-TPD), poly (9-vinyl carbazole) (PVK), and polytriarylamine (PTAA).

[0020] Further, the electron transport layer material includes one or more of 4,6-bis(3,5-di(3-pyridyl)phenyl)-2-methylpyrimidine (B3PYMPM), 1,3,5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), zinc oxide and titanium dioxide;

[0021] The material of the electron injection layer includes cesium carbonate; the cathode includes an Al electrode.

[0022] Furthermore, the thickness of the anode is in the range of 100-150 nm; the thickness of the hole transport layer is 40-50 nm; the thickness of the electron transport layer is 55-70 nm; the thickness of the electron injection layer is 1-2 nm; and the thickness of the cathode is 100-150 nm.

[0023] A method for preparing a perovskite light-emitting diode is provided, the method comprising the steps of:

[0024] S101. The anode ITO conductive glass as the substrate is subjected to plasma gas treatment to reduce the work function of the ITO surface; improve the wettability of the film surface;

[0025] S102. Spin coating the hole transport layer material on the anode at a rotation speed of 4000 rpm for 40 to 60 seconds. After the spin coating is completed, heat to 150° C. and anneal for 15 to 20 minutes;

[0026] S103. Spin-coating the perovskite light-emitting layer with a light-emitting layer material (a green light perovskite light-emitting material precursor solution), dissolving the three-dimensional green light perovskite CsPbBr3 as the light-emitting layer material in dimethyl sulfoxide (DMSO), with a concentration of 0.3 mol / L after dissolution, a spin-coating speed of 2000 rpm, a spin-coating time of 50-60 seconds, and heating to 37-45° C. for annealing for 1 minute after spin-coating;

[0027] S104. After the spin coating of the light-emitting layer material is completed, the perovskite light-emitting layer is cooled to room temperature, and the perovskite light-emitting layer is post-treated with a TPBi acetone solution, the concentration of which is 3-4 mg / ml, and the TPBi acetone solution is spin-coated on the perovskite light-emitting layer at a rotation speed of 2000 rpm for 30-40 seconds;

[0028] S105. Transfer the spin-coated device to a vacuum deposition chamber at a temperature below 5×10 -4 Under a vacuum degree of Pa, the electron transport layer material is deposited at a rate of 1~2Å / s; the electron injection layer material is deposited at a rate of 0.08Å / s; and the cathode electrode material is deposited at a rate of 2~3Å / s. After the deposition is completed, a perovskite light-emitting diode is obtained.

[0029] The beneficial effects of the present invention are:

[0030] (1) During the high-temperature annealing process of the perovskite precursor solution, a large number of disordered nucleation sites will be formed. The crystals that grow rapidly along the disordered nucleation sites are usually accompanied by the generation of a large number of defects. At the same time, when cesium bromide and lead bromide are directly dissolved in the solvent and spin-coated to form a perovskite film, a non-target crystalline phase film is easily formed. By pre-synthesizing pure phase CsPbBr3 powder and adding a certain proportion of CsBr when preparing the perovskite precursor solution, the perovskite is passivated in the bromine-rich state. At the same time, low-temperature annealing and excessive CsBr additives induce the perovskite crystals to grow along the (110) crystal plane that is conducive to carrier transport. At the same time, low temperature can delay the crystallization of perovskite, so that the perovskite has sufficient time to grow in an orderly manner, inhibiting the disordered growth of clusters and crystals, and improving the film quality.

[0031] (2) TPBi acetone solution is used to treat the upper surface of the perovskite light-emitting layer film. Perovskite will inevitably dissociate during crystallization, and the dissociated phase is not conducive to the improvement of device performance. First, acetone can wash away the dissociated phase that is not firmly attached to the surface of the perovskite, exposing the defects on the surface of the film. At the same time, it can also dissolve and recrystallize the upper surface of the film. At the same time, TPBi in the solution will enter the film grain boundaries, hole defects and other places along the solution to fill the film defects, thereby passivating the potential defects inside the film and on the upper surface on a large scale, further reducing the film defects and significantly improving the external quantum efficiency and brightness of the light-emitting diode. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The device data of Example 1 and Original Example 1, a) is the device current density-voltage-brightness curve, b) is the device external quantum efficiency-voltage curve, c) is the electroluminescence spectrum;

[0033] Figure 2 The chemical structure diagram of TPBi after surface treatment on the perovskite light-emitting layer;

[0034] Figure 3 Schematic diagram of the structure of the perovskite light-emitting diode device of Example 2 and Original Example 2;

[0035] Figure 4 The steady-state fluorescence spectra of the perovskite of Example 2 and Original Example 2;

[0036] Figure 5 The device data of Example 2, a) is the device current density-voltage-brightness curve, b) is the external quantum efficiency-voltage curve, c) is the electroluminescence spectrum;

[0037] Figure 6 The device data of the original example 2, a) is the device current density-voltage-brightness curve, b) is the external quantum efficiency-voltage curve, and c) is the electroluminescence spectrum. DETAILED DESCRIPTION

[0038] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0039] The conductive substrate ITO substrate, glass cleaning solution, and PbBr2 used in this embodiment were purchased from Liaoning Youxuan Technology Co., Ltd. CsBr, Cs2CO3, and 48% hydrobromic acid were purchased from Sigma, TPBi and B3PYMPM were purchased from Xi'an Yuri Solar Energy Technology Co., Ltd., and Al was purchased from Fujian Zijin Yingfeixun Applied Materials Co., Ltd.

[0040] The present invention is based on pure phase all-inorganic CsPbBr3 powder obtained by dissolution precipitation recrystallization, and then the pre-synthesized powder is configured into a perovskite precursor solution, and a perovskite film is prepared, annealed, and then a post-treatment solution is spin-coated on the surface of the perovskite film to obtain a post-treated perovskite light-emitting layer, and then an electron transport layer, an electron injection layer and a cathode material are prepared by vapor deposition in sequence to obtain a perovskite light-emitting device.

[0041] Example 1

[0042] In this embodiment 1, a method for preparing a perovskite light-emitting diode by pre-synthesizing pure phase all-inorganic CsPbBr3 powder includes an anode ITO conductive glass, a hole transport layer, a perovskite light-emitting layer, a post-treatment layer, an electron injection layer and a cathode electrode.

[0043] The thickness of the anode ITO conductive glass is 0.7mm, the thickness of ITO is 150nm, the size is 16mm×16mm, and the resistance is 15Ω / m 2 The hole transport layer uses PEDOT:PSS solution, the perovskite light-emitting layer is prepared by pre-combining CsPbBr3 powder and CsBr dissolved in DMSO, the post-treatment layer uses TPBi acetone solution, and the electron transport layer uses B3PYMPM. The electron injection layer uses Cs2CO3, and the cathode uses Al.

[0044] The specific preparation method of the precursor solution in this embodiment 1 is as follows:

[0045] Preparation of pure phase all-inorganic CsPbBr3 powder: 3.65 g of PbBr2 was dissolved in 15 ml of 48% volume fraction hydrobromic acid aqueous solution to form a light yellow solution. Then 2.13 g of CsBr was dissolved in 5 ml of deionized water, and then added dropwise to the formed PbBr2-HBr solution within 5 min to form an orange-yellow precipitate, and the solution was stirred for another hour. Finally, the precipitate CsPbBr3 was collected by suction filtration, washed twice with anhydrous ethanol, and vacuum dried at 60 °C for 12 hours before use.

[0046] CsPbBr3 (347.9 mg) and CsBr (51.1 mg) were dissolved in 2 ml of DMSO solvent, and the mixture was stirred overnight at room temperature under a nitrogen atmosphere.

[0047] The specific process of preparing the perovskite light-emitting diode device by pre-synthesizing the pure phase all-inorganic CsPbBr3 powder in this embodiment 1 is as follows:

[0048] (1) First, use acetone to ultrasonically clean the ITO glass for 20 minutes, then scrub it with glass cleaning fluid for 10 minutes, then rinse it with deionized water, and then rinse the ITO surface with anhydrous ethanol. Finally, place the ITO in anhydrous ethanol and ultrasonically clean it for 20 minutes twice, and blow dry the ITO glass surface with nitrogen for later use;

[0049] (2) The ITO glass in (1) was then cleaned with 30% plasma power for 5 min and quickly transferred to an air glove box;

[0050] (3) Spin-coat the PEDOT:PSS solution on the ITO glass at a spin-coating speed of 4000 rpm for 40 seconds and an annealing temperature of 150°C for 15 minutes.

[0051] (4) The device with the hole transport layer prepared in (3) was quickly transferred to a nitrogen glove box for spin coating of the perovskite light-emitting layer. 30 μl of the perovskite precursor solution was taken with a pipette and applied to the hole transport layer at 2000 rpm / 60 s. After the spin coating, an annealing treatment was performed at 45 °C / 1 min.

[0052] (6) After step (4) is completed, the device is transferred into a high vacuum evaporation chamber and an electron transport layer B3PYMPM (70 nm), an electron injection layer Cs2CO3 (1 nm), and a cathode Al (100 nm) are sequentially deposited.

[0053] Original Example 1

[0054] The light emitting diode of original example 1 is the same except for the preparation method of the precursor solution.

[0055] The specific preparation method of the precursor solution in this original example 1 is as follows:

[0056] CsPbBr3 (220.2 mg) and CsBr (178.8 mg) were dissolved in 2 ml of DMSO solvent and stirred overnight at room temperature under nitrogen atmosphere.

[0057] The specific process of preparing the perovskite light-emitting diode device with all-inorganic CsPbBr3 powder in this original example 1 is as follows:

[0058] (1) First, use acetone to ultrasonically clean the ITO glass for 20 minutes, then scrub it with glass cleaning fluid for 10 minutes, then rinse it with deionized water, and then rinse the ITO surface with anhydrous ethanol. Finally, place the ITO in anhydrous ethanol and ultrasonically clean it for 20 minutes twice, and blow dry the ITO glass surface with nitrogen for later use;

[0059] (2) The ITO glass in (1) was then cleaned with 30% plasma power for 5 min and quickly transferred to an air glove box;

[0060] (3) Spin-coat the PEDOT:PSS solution on the ITO glass at a spin-coating speed of 4000 rpm for 40 seconds and an annealing temperature of 150°C for 15 minutes.

[0061] (4) The device with the hole transport layer prepared in (3) was quickly transferred to a nitrogen glove box for spin coating of the perovskite light-emitting layer. 30 μl of the perovskite precursor solution was taken with a pipette and applied to the hole transport layer at 2000 rpm / 60 s. After the spin coating, an annealing treatment was performed at 45 °C / 1 min.

[0062] (6) After step (4) is completed, the device is transferred into a high vacuum evaporation chamber and an electron transport layer B3PYMPM (70 nm), an electron injection layer Cs2CO3 (1 nm), and a cathode Al (100 nm) are sequentially deposited.

[0063] See also Figure 1 , to compare the photoelectric performance of Example 1 and Original Example 1, the perovskite light-emitting diode devices of Example 1 and Original Example 1 were tested, and the luminous area during the period was 4mm 2 Compared with the original example 1, the example 1 has higher external quantum efficiency, higher brightness and lower current density at the same driving voltage, and the electroluminescence peak has no obvious shift.

[0064] Example 2

[0065] In this embodiment 2, a method for preparing a perovskite light-emitting diode by pre-synthesizing pure phase all-inorganic CsPbBr3 and surface treating the light-emitting layer is provided. Embodiment 2 is the same as Embodiment 1 except that post-treatment is added to the perovskite film.

[0066] In this embodiment 2, pure phase all-inorganic CsPbBr3 is pre-synthesized, and the specific process of preparing the perovskite light-emitting diode device by surface treatment on the light-emitting layer is as follows:

[0067] (1) First, use acetone to ultrasonically clean the ITO glass for 20 minutes, then scrub it with glass cleaning fluid for 10 minutes, then rinse it with deionized water, and then rinse the ITO surface with anhydrous ethanol. Finally, place the ITO in anhydrous ethanol and ultrasonically clean it for 20 minutes twice, and blow dry the ITO glass surface with nitrogen for later use;

[0068] (2) The ITO glass in (1) was then cleaned with 30% plasma power for 5 min and quickly transferred to an air glove box;

[0069] (3) Spin-coat the PEDOT:PSS solution on the ITO glass at a spin-coating speed of 4000 rpm for 40 seconds and an annealing temperature of 150°C for 15 minutes.

[0070] (4) The device with the hole transport layer prepared in (3) was quickly transferred to a nitrogen glove box for spin coating of the perovskite light-emitting layer. 30 μl of the perovskite precursor solution was taken with a pipette and applied to the hole transport layer at 2000 rpm / 60 s. After the spin coating, an annealing treatment was performed at 45 °C / 1 min.

[0071] (5) After the perovskite film is annealed and cooled, use a pipette to draw 50 μl of TPBi acetone solution (4 mg / ml) and apply it on the perovskite film. The spin coating condition is 2000 rpm / 60 s. The structural formula of TPBi can be found in Figure 2 ;

[0072] (6) After step (5) is completed, the device is transferred into a high vacuum evaporation chamber to deposit the electron transport layer B3PYMPM (70nm), the electron injection layer Cs2CO3 (1nm), and the cathode Al (100nm) in sequence. The device structure is as follows: Figure 3 a).

[0073] Original Example 2

[0074] The components of the light emitting diode of the original example 2 are exactly the same as those of the example 1. The detailed preparation method of the device is as shown in the example 1, and the device structure is as shown in the example 1. Figure 3 b).

[0075] See also Figure 4 , are the photoluminescence intensities of Example 2 and Original Example 2. Compared with Original Example 2, the photoluminescence intensity of Example 2 is much higher than that of Original Example 2, and the peak position has not shifted, indicating that the perovskite film post-treated by TPBi has better performance.

[0076] See also Figure 5-Figure 6 , which are the comparisons of the photoelectric performances of the devices of Example 2 and Original Example 2, respectively. Compared with Original Example 2, Example 2 has higher brightness under the same driving voltage, and the external quantum efficiency of Example 2 is much higher than that of Original Example 2, reaching 10.78%, and there is no obvious shift in the electroluminescent peak.

[0077] The preparation of perovskite light-emitting diodes by pre-synthesizing all-inorganic pure phase CsPbBr3 powder can effectively improve the device performance of all-inorganic green light perovskite light-emitting diodes. The preparation of efficient all-inorganic green light perovskite light-emitting diodes is achieved by introducing TPBi as a post-treatment layer on the upper surface of perovskite. This shows that the use of this post-treatment method for the material is positive and effective in improving the performance of perovskite devices.

[0078] The above is only a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not deviate from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing an all-inorganic green light perovskite luminescent layer material, characterized in that: The method steps include: S1. Dissolve CsBr in deionized water to prepare a CsBr solution; S2. PbBr2 is dissolved in a 48% by volume HBr solution to prepare a PbBr2-HBr solution; S3. The CsBr solution was added dropwise to the PbBr2-HBr solution to form a mixed solution. After an orange-yellow precipitate was formed in the mixed solution, the mixed solution was stirred continuously, and the precipitate CsPbBr3 was collected by filtration. S4. Wash the precipitated CsPbBr3 twice with anhydrous ethanol and dry it at 60°C in a vacuum environment to obtain a dry precipitated CsPbBr3 powder as a perovskite light-emitting layer material.

2. The method for preparing an all-inorganic green light perovskite luminescent layer material according to claim 1, characterized in that: In the S1, 2.13 g of CsBr was dissolved in 5 ml of deionized water.

3. The method for preparing an all-inorganic green light perovskite luminescent layer material according to claim 1, characterized in that: 3.65 g of PbBr2 in S2 is dissolved in 15 ml of a 48% by volume aqueous solution of hydrobromic acid.

4. The method for preparing an all-inorganic green light perovskite luminescent layer material according to claim 1, characterized in that: The CsBr solution in S3 is added dropwise for 5 minutes.

5. The method for preparing an all-inorganic green light perovskite luminescent layer material according to claim 1, characterized in that: The stirring time in S3 is 1 hour, and the vacuum drying time is 12 hours.

6. A perovskite light-emitting diode, characterized in that: The diode comprises an anode, a hole transport layer, a perovskite light-emitting layer, a post-processing layer, an electron transport layer, an electron injection layer and a cathode, which are arranged in sequence from bottom to top, and the perovskite light-emitting layer is located between the hole transport layer and the electron transport layer; Wherein, the perovskite light-emitting layer material is CsPbBr3; Wherein, the thickness of the perovskite light-emitting layer is 60-80 nm; Wherein, the anode comprises indium tin oxide conductive glass; The hole transport layer material includes one or more of poly (3,4-ethylenedioxythiophene:polystyrene sulfonate) (PEDOT:PSS), 4-butyl-N,N-diphenylaniline homopolymer (poly-TPD), poly (9-vinyl carbazole) (PVK), and polytriarylamine (PTAA).

7. A perovskite light-emitting diode according to claim 6, characterized in that: The electron transport layer material includes one or more of 4,6-bis(3,5-di(3-pyridyl)phenyl)-2-methylpyrimidine (B3PYMPM), 1,3,5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), zinc oxide and titanium dioxide; The material of the electron injection layer includes cesium carbonate; the cathode includes an Al electrode.

8. The perovskite light-emitting diode according to claim 6, characterized in that: The thickness of the anode is in the range of 100-150 nm; the thickness of the hole transport layer is 40-50 nm; the thickness of the electron transport layer is 55-70 nm; the thickness of the electron injection layer is 1-2 nm; and the thickness of the cathode is 100-150 nm.

9. A method for preparing a perovskite light-emitting diode, characterized in that: The method steps include: S101. Treat the anode ITO conductive glass as the substrate with plasma gas to reduce the work function of the ITO surface. S102. Spin coating the hole transport layer material on the anode at a rotation speed of 4000 rpm for 40 to 60 seconds. After the spin coating is completed, heat to 150° C. and anneal for 15 to 20 minutes; S103. Spin-coating the perovskite light-emitting layer with a light-emitting layer material, dissolving the three-dimensional green light perovskite CsPbBr3 as the light-emitting layer material in dimethyl sulfoxide (DMSO) to a concentration of 0.3 mol / L after dissolution, spinning at a speed of 2000 rpm for 50 to 60 seconds, and heating to 37 to 45° C. for annealing for 1 minute after the spin coating is completed; S104. After the spin coating of the light-emitting layer material is completed, the perovskite light-emitting layer is cooled to room temperature, and the perovskite light-emitting layer is post-treated with a TPBi acetone solution, the concentration of which is 3-4 mg / ml, and the TPBi acetone solution is spin-coated on the perovskite light-emitting layer at a rotation speed of 2000 rpm for 30-40 seconds; S105. Transfer the spin-coated device to a vacuum deposition chamber at a temperature below 5×10 -4 Under a vacuum degree of Pa, the electron transport layer material is deposited at a rate of 1~2Å / s; the electron injection layer material is deposited at a rate of 0.08Å / s; and the cathode electrode material is deposited at a rate of 2~3Å / s. After the deposition is completed, a perovskite light-emitting diode is obtained.